The Impact of Joyful Learning Model on Motivation and Mathematics Learning Outcomes in Class X SMA Negeri 3 Salatiga - Dewi Handayani; Agus Ariyanto (Universitas Mercu Buana Yogyakarta, 2021)
This study aims to determine whether there is an effect of the Joyful Learning learning model on motivation and mathematics learning outcomes. This type of research is quasi-experimental research with the design of the randomize control group pretest-posttest design. The population in this study were students of class X SMA Negeri 3 Salatiga Semester 2 of the 2015/2016 academic year. The sample was taken by using cluster random sampling technique and it was obtained that the students of class X.6 (32 students) were the experimental class which was taught using the Joyful Learning learning model, X.7 (34 students) was the control class which was taught using the conventional learning model. The instruments used in this study were the UTS and posttest value data to measure learning outcomes and a questionnaire to measure student learning motivation. The test instrument validation trial and questionnaire included expert validation. The data analysis used was the normality test with the Kolmogorov-Smirnov test, the homogeneity test with the Levene test and the mean difference test with the Independent Sample t-test. All tests were carried out with a significance level of 5% with the calculation tool SPSS 16.0.0 software. The results of the initial conditions both for learning motivation and learning outcomes are in a balanced condition. The results of hypothesis testing using the independent sample t-test for the final condition of learning motivation and the Mann-Whitney U-Test for the final ability of learning outcomes. The significant value for learning motivation is 0.443 0.05. This shows that there is no effect of the joyful learning model on learning motivation of class X SMA Negeri 3 Salatiga. The significant value for the final ability of learning outcomes is 0.357 0.05. This shows that there is no influence of the Joyful Learning model on the learning outcomes of class X SMA Negeri 3 Salatiga. It can be concluded that the Joyful Learning learning model has no effect on the motivation and learning outcomes of students in class X SMA Negeri 3 Salatiga.